Analysis of Soil Heat Propagation Properties for Determining the Optimal Soil Type in Passive Photovoltaic Cooling Systems - Abdurrohman Abdurrohman; Rindi Wulandari (Al-Makki Publisher, 2026)
Rising photovoltaic (PV) module operating temperature substantially reduces conversion efficiency, motivating passive, low-cost cooling strategies that avoid extra electrical energy consumption. Grounding-based passive cooling, using surrounding soil as a heat-dissipating medium, offers a promising alternative; however, prior studies have mostly characterized soil thermal properties in isolation rather than directly comparing soil types under a unified, real-time measurement protocol relevant to PV cooling. This study aims to analyze and compare the thermal conductivity of clay and coastal sandy soil as candidate passive-cooling media, while examining how moisture content and pH influence heat propagation. A quantitative experimental approach was employed using the Transient Line Heat Source (TLHS) technique, implemented through an ESP32 microcontroller integrated with a DS18B20 temperature sensor and a soil moisture/pH probe for automatic, real-time data acquisition. The system operated stably in an integrated manner, producing consistent temperature-time data for conductivity calculation. Results showed clay had an average thermal conductivity of 1.133 W/mK at 74.25% moisture content, while coastal sandy soil reached 1.595 W/mK at 81.25% moisture content, an increase of about 40.78%, indicating moisture content, alongside soil type, is a key determinant of heat propagation. These findings imply soils with higher natural moisture retention are more promising passive-cooling media, offering practical guidance for designing low-cost, energy-independent cooling solutions for tropical, ground-coupled PV installations.